Potensi Tanaman Rempah dan Obat Tradisional Indonesia Sebagai Sumber Bahan Pangan Fungsional - Irmanida Batubara; Muhammad Eka Prastya (xxxx-xxxx, 2020)
Irmanida B, Prastya ME.  2020.  The potency of indonesian spices and traditional medicine plants as for the sources of fungtional foods ingredients. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).As a public knowledge pertanining healthy lifestyle increases, the need for food that has health benefits also increases. This food is popular as a functional food, which is not only contains nutrients, but also has a physiological benefits to prevent or cure diseases. One of the sources of functional food ingredients in Indonesia are spices and medicinal plants which are known containing various types of phytochemical compounds. Numerous reports showed a health benefits of phytochemical compounds derived from spices and medicinal plants such as ginger (Zingiber officinale), turmeric (Curcuma domestica), cardamom (Amomum cardamomum), legetan warak (Adenostemma lavenia), the god’s crown (Phaleria macrocarpa), and lambo guava (Psidium guajava). The phytochemical compounds from those plants are recognized to prevent or cure various diseases including high blood pressure, cancer, diabetes, flu, coughs, sore throat, etc. Functional food products based on spices and medicinal from these 6 plants are usually in the form of jamu, instant healthy drinks, tea, juices, sweets, syrups, etc. Functional food based on Indonesian spices and medicinal plants has the potential to be developed because of its high demand, adequate production and a lot of research that has been conducted. Although the Indonesian government has made the regulations on special nutritious food, these regulations are considered insufficient. Therefore, the government needs to make a specific and comprehensive regulations on functional food in Indonesia, specifically those based on spices and medicinal plants.